(untitled) (Research, Society and Development, 2025)
Neonatal hearing screening indicate during the perinatal period, consists of conducting tests and retests using physiological and electrophysiological measures of hearing in infants. The aim of this study was to analyze the results of Auditory Brainstem Responses (ABR) from 149 children age average of 31 months, with or without risks for hearing loss evaluated at a University Hospital between 2022 and 2024. The identification data, complaints/referrals, and the results of the ABR were checks. The sample was divided into seven groups according to the recommendation of the Joint Committee on Infant Hearing and spontaneous demand: 1) with risk indicator form hearing impairment, 2) with failure on the newborn hearing screening, 3) with a complaint of hearing loss, 4) Down’s Syndrome, 5) with neuropsychonmotor developmental delay, 6) Autism Spectrum Disorder, and 7) needing diagnostic confirmation. Fourteen children showed results the confirmed involvement of middle and inner ear and auditory nerve. It was possible to conclude the audiological diagnosis of the entire sample, which revealed a 10,0% incidence of hearing impairment. This fact emphasized the importance of the need for intervention to minimize the negative impact of deafness on overall development of the pediatric population. The results imply that there is a failure in the procedures of neonatal hearing screening in the auditory health care service in the state.